Profile of MYH9 SNP RS3752462 Gene Polymorphism in Chronic Kidney Disease (CKD) Patients with Hypertension - Nabiilah Nuur Ainii Heryanti; Muhammad Taufiq Qurrohman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chronic kidney disease (CKD) and hypertension are closely related conditions and can be influenced by genetic factors, including polymorphisms in the Myosin Heavy Chain 9 (MYH9) gene. The SNP rs3752462 in the MYH9 gene is known to be associated with impaired kidney function. This study aims to describe the genotype pattern of the MYH9 rs3752462 SNP polymorphism in patients with chronic kidney disease and hypertension at UNS Hospital. This is a descriptive study with a molecular analysis approach. A total of 10 blood samples were collected. Polymorphism detection was performed using the Polymerase Chain Reaction–Restriction Fragment Length Polymorphism (PCR-RFLP) method with the RsaI restriction enzyme. The results showed that all samples were successfully amplified, producing a PCR product of approximately 421 bp. The DNA bands observed in all samples did not form a consistent combination and did not match the expected genotype reference standard. In addition, the appearance of additional bands outside the target fragment size, therefore the results of this study do not adequately represent the MYH9 SNP rs3752462 gene polymorphism in the studied samples. Conclusion: Further examination is needed using other modern methods such as DNA sequencing and larger sample sizes to obtain appropriate results.